Controlling the porosity and crystallinity of MgO catalysts by addition of surfactant in the sol-gel synthesis - Possato, Luiz G. [UNESP]; Pereira, Elen [UNESP]; Gonçalves, Rosembergue G.L. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Martins, Leandro [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 2018)
This study presents an easy route to induce pore formation, increase the specific surface area and control the crystallite size of magnesium oxides obtained using the sol-gel method with addition of Pluronic P123 surfactant. The structural characteristics of the materials were evaluated using X-ray diffraction, N2 physisorption isotherms, mercury intrusion porosimetry, scanning electron microscopy and CO2 temperature programmed desorption. The catalytic properties were assessed using the Knoevenagel condensation reaction. The results showed a systematic decrease of the magnesium oxide crystallinity with increased concentration of the surfactant used in the synthesis. This was associated with increase of the magnesium oxide BET area from 2 m2/g to over 50 m2/g, as well as the formation of pores in the macropore region, as confirmed by microscopy images. In addition, the surface modification resulted in CO2 chemisorption increasing from 378 μmol/g, for the pristine MgO sample, to 1529 μmol/g, for the porous sample, accompanied by an increase in the concentration of strong basic sites. The most porous sample presented the highest catalytic activity in the Knoevenagel condensation reaction.
Keywords: Basic catalysts; Knoevenagel condensation; Porous materials; Porous MgO; Sol-gel